Subaltern Body: Politics and Poetics of Agency in Mahasweta Devi’s “Draupadi” (1978) (Far Western Review, 2024)
Mahasweta Devi (1926–2016) employs mythical figure Draupadi from the Mahabharata as the voice of Naxalites of Bengal in her short fiction “Draupadi” (1978) which sits in the nexus of Bengal’s societal transformation in the 1970s, hoping to end caste-based discrimination and economic exploitation in her society. This study examines the resistance of Santhal tribal women in India’s historical Naxalite insurgency to retain their dignity and identity, establishing their own agency and solidarity through “Draupadi” (1978). Furthermore, it examines the text through the lens of agency in relation to the subaltern body as a site of resistance, drawing upon Michael Garnett, Gramsci, and Spivak. Devi’s protagonist Dopdi, a Naxalite activist, is chased and raped in an attempt to suppress insurgent organizations, resulting in the loss of their land and identity. But the so-called ‘subaltern’ ultimately resists and ‘speaks’ when pushed to the ultimate margin. Finally, Dopdi emerges as empowered who displays an unusual form of resistance. The transformation of the protagonist from powerlessness to empowered quest of agency, emerging as site of resistance dismantles the social hierarchies and oppressive ideologies figuratively and literally. Using Draupadi as a prism, the author analyzes her society and offers a perceptive assessment of its current situation; and speaks symbolically through her literary imaginings. Devi’s politically conscious persona, Draupadi, opposes power and seeks to rethink and rewrite the historical and geopolitical circumstances through the lenses of agency and inner freedom of a subaltern body and sexuality as the locus of resistance.